Inhibition of various gram-positive and gram-negative bacteria growth on selenium nanoparticle coated paper towels - Wang Q (Dove Medical Press, 2015)
Qi Wang,1 Philip Larese-Casanova,2 Thomas J Webster3,41Department of Bioengineering, College of Engineering, Northeastern University, Boston, MA, USA; 2Department of Civil and Environmental Engineering, College of Engineering, Northeastern University, Boston, MA, USA; 3Department of Chemical Engineering, College of Engineering, Northeastern University, Boston, MA, USA; 4Center of Excellence for Advanced Materials Research, King Abdulaziz University, Jeddah, Saudi ArabiaAbstract: There are wide spread bacterial contamination issues on various paper products, such as paper towels hanging in sink splash zones or those used to clean surfaces, filter papers used in water and air purifying systems, and wrappings used in the food industry; such contamination may lead to the potential spread of bacteria and consequent severe health concerns. In this study, selenium nanoparticles were coated on normal paper towel surfaces through a quick precipitation method, introducing antibacterial properties to the paper towels in a healthy way. Their effectiveness at preventing biofilm formation was tested in bacterial assays involving Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus epidermidis. The results showed significant and continuous bacteria inhibition with about a 90% reduction from 24 to 72 hours for gram-positive bacteria including S. aureus and S. epidermidis. The selenium coated paper towels also showed significant inhibition of gram-negative bacteria like P. aeruginosa and E. coli growth at about 57% and 84%, respectively, after 72 hours of treatment. Therefore, this study established a promising selenium-based antibacterial strategy to prevent bacterial growth on paper products, which may lead to the avoidance of bacteria spreading and consequent severe health concerns.Keywords: selenium nanoparticles, paper towels, antibacterial